PERENCANAAN STRATEGI PUBLIC RELATIONS DALAM MEMBENTUK CORPORATE BRANDING NET. SEBAGAI TELEVISI MASA KINI - Vidya Fitri Ferdiansyah; Vanya Kirana Kandialarasati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
In this global era of digitalization, it turns out that television is still the strongestmass media among other medias. NET., one of Indonesian television stationsutilize this digital phenomenon as the program distribution process whichincludes using multiplatform. NET. utilize multiplatform as one of its publicrelations strategy to form its corporate branding as Televisi Masa Kini. NET. as arelatively young television stasion in Indonesian television industry hassucceeded in becoming top of mind in the mind of people. Therefore, researchersinterested to make this research of public relations strategy that used by NET.’spublic relations in order to form its corporate branding as Televisi Masa Kini byusing qualitative approach and in-depth interviews. The result of this research isthat NET. used all the steps in public relations strategy planning that has fourphases which is formative research, strategy, tactics, and evaluative researchthat includes nine steps and it’s able to help NET. form its corporate branding asTelevisi Masa Kini. The findings in this research is NET. Good People, which isone of the NET.’s public relations program as one of the most effective publicrelations stategy to form NET.’s corporate branding as Televisi Masa Kini.